Penerapan Sistem Gadai Emas pada Bank Syariah Indonesia KCP Gunung Tua - Rizki Munaito Siregar; Reni Ria Armayani Hasibuan (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
Bank Syariah Indonesia KCP Gunung Tua is a financial institution that mediates community needs through its various products and services. One of the products owned by BSI KCP Gunung Tua is a pawn financing product (rahnemas) which is financing for productive and consumptive needs provided to all people who need funds with gold as their marhun. constraints and obstacles faced by banks in financing gold pawning at BSI KCP Gunung Tua. This study uses a qualitative research method, in which researchers will describe or describe the gold pawn system at the Indonesian Sharia Bank KCP Gunung Tua. Based on the research results, it was found that the gold pawn system at Bank Syariah Indonesia KCP Gunung Tua has implemented a service system that is easy, fast, cheap and safe and is in accordance with DSN MUI Fatwa No.25/DSN-MUI/III/2002 dated 26 June 2002 about rahn which explains the provisions of pawning practices in accordance with Islamic law. One of them is "the cost of maintaining and storing marhun cannot be determined based on the amount of the loan". forgot the payment due date.